The Influence of Community Efforts on Malaria Vector Density - Gudipung, Hilarius Yosef Muda (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Malaria still becomes a public health problem, especially on the outside of Java and Bali. Increasing morbidity rate of malaria is one thing caused by malaria vector that exist in endemic area. This study aims to study the incidence of malaria cases and the effect of community efforts on malaria vectors density. This research is cross sectional and using systematic random sampling method. Respondents were 92 samples in endemic and non-endemic villages. The variables of this research were vector density as bound variable, while mosquito repellent, mosquito breeding sites cleaning, spray mosquito coil as independent variable and analyzed using regression logistic test. The results of this study showed that the use of mosquito repellents (p = 0.077), OR = 2,304 (95% Cl 0,913-5,015), mosquito breeding site cleaning (p = 0,028) OR = 2,741 (95% Cl 1,117-6,724), spray mosquito repellent (p = 0,006), OR = 3,799 (95% Cl 1,458-9,899). While for the vector density of Labuhan Lombok village belong to high category (2.03) and for Pohgading village included in low category (0,50). Health education activities about malaria disease still need to be improved, to avoid mosquito bites should be understood how to control the mosquito, so mosquito density can be reduced. It is expected that the community participates in the prevention of malaria in their area.  Keywords: Malaria, mosquito, vector density